(untitled) (Physical Education, Health and Social Sciences, 2026)
Motor skill acquisition is crucial for physical, cognitive, and social development, especially among students with hearing impairments who rely heavily on visual and kinesthetic cues. This study examined the comparative effects of autocratic, democratic, and laissez-faire coaching styles on motor skill acquisition in hearing-impaired male students enrolled in the Diploma in Special Education at Government Degree College of Special Education, Dera Ghazi Khan. A quasi-experimental pre-test & post-test design was employed with 30 purposively selected participants, divided equally into three coaching groups. A standardized motor skill test battery measured performance accuracy, coordination, and technique before and after a 6-week intervention. Descriptive statistics indicated that all groups improved significantly (p < 0.001), with the democratic group achieving the highest gain (Mean = 25.60), followed by autocratic (Mean = 15.30) and laissez-faire (Mean = 9.20). One-way ANOVA confirmed significant differences in post-test scores among the groups (F = 45.62, p < 0.001). Post-hoc Tukey HSD tests revealed that democratic coaching outperformed both autocratic and laissez-faire styles, while autocratic was more effective than laissez-faire. The findings suggest that democratic coaching, which combines structured guidance with active learner participation, is most effective for enhancing motor skills in hearing-impaired students. Autocratic coaching supports immediate skill improvement but limits autonomy, whereas laissez-faire provides minimal gains. These results highlight the importance of inclusive and participatory teaching strategies. Future research should explore larger samples, long-term retention, hybrid coaching approaches, broader age ranges, and motivational outcomes to optimize adapted physical education.